(untitled) (American Journal of Islam and Society, 2016)
Shaykh Taha Jabir al-‘Alwani – professor of jurisprudence (fiqh) and the principles of jurisprudence (uṣūl al-fiqh); president of the School of Islamic and Social Sciences (SISS), which later became the Graduate School of Islamic and Social Sciences (GSISS); president of the Fiqh Council of North America, holder of the Imam Al- Shafi‘i Chair in Islamic Legal Theory at Corboda University; founding member and president of the International Institute of Islamic Thought (IIIT); founder-member of the Council of the Muslim World League in Makkah; member of the Organization of Islamic Cooperation’s Islamic Fiqh Academy in Jeddah; prolific writer; and world renowned Islamic scholar and expert in Islamic legal theory, jurisprudence, the principles of jurisprudence, Qur’anic sciences, and general Islamic thought – passed away on March 4, 2016, at Ireland’s Shannon Airport while stopping over on his way from Cairo to Washington, DC. An intellectual giant, friend, father, husband, and teacher, he leaves an immense void in the lives of many people. The Muslim world mourns his loss and is the poorer for it. Shaykh Taha spent his life serving humanity and the truth, working tirelessly not only to elucidate the principles and methodology of Islamic jurisprudence, but also to remove many of the myths and prejudices that had, over time, become entwined with Muslim cultural traditions and gained a strong foothold in the Muslim mind. Shaykh Taha always took account of Islam as it is being practised in the modern world. For example, his seminal work Apostasy in Islam (2011), a masterful example of historical and scriptural ...